Distinct cerebral 18F-FDG PET metabolic patterns in anti-N-methyl-D-aspartate receptor encephalitis patients with different trigger factors. (February 2021) - Ge, Jingjie; Deng, Bo; Guan, Yihui; Bao, Weiqi; Wu, Ping; Chen, Xiangjun; Zuo, Chuantao
Aim: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is a subgroup of treatable autoimmune encephalitis, characterized by rapid development of psychosis, cognitive impairments and seizures. Etiologically, anti-NMDAR encephalitis could be divided into three subgroups, which are paraneoplastic (especially associated with ovarian teratoma), viral encephalitis-related and cryptogenic. Each type is different in clinical course, treatment strategies and prognosis. In this study, we aim to investigate whether anti-NMDAR encephalitis patients with different trigger factors exhibit distinct cerebral metabolic patterns detected by 18 F-fluorodeoxyglucose positron emission tomography imaging. Methods: 24 patients with anti-NMDAR encephalitis in acute phase from Huashan Hospital, Fudan University (Shanghai, China) were recruited in this study. Each patient was classified into one of etiological subgroups. Positron emission tomography images of individual patients were analyzed with both routine visual reading and computer-supported reading by comparison with those of the same 10 healthy controls using a voxel-wise statistical parametric mapping analysis. Results: Patients in both the cryptogenic (13 patients) and paraneoplastic (five patients) subgroups showed hypermetabolism in the frontal-temporal lobes and basal ganglia, covarying with hypometabolism in the occipital regions. Notably, the abnormal metabolism was usually asymmetric in the cryptogenic subgroup, but relatively symmetric in the paraneoplastic subgroup. Moreover, the other six patients secondary to viral encephalitis presented with significant hypometabolism in the bilateral occipital regions, as well as in the unilateral temporal lobes and part of basal ganglia (also is virus infection side), but hypermetabolism in the contralateral temporal areas. Conclusion: This study revealed that patients with anti-NMDAR encephalitis triggered by different factors presented distinct cerebral metabolic patterns. Awareness of these patterns may help to better understand the varying occurrence and development of anti-NMDAR encephalitis in each subgroup, and could offer valuable information to the early diagnosis, treatment and prognosis of this disorder. Trial registration number: ChiCTR2000029115 (Chinese clinical trial registry site, http://www.chictr.org )